1999
DOI: 10.3928/0098-9134-19990301-11
|View full text |Cite
|
Sign up to set email alerts
|

Developing Individualized Care in Nursing Homes

Abstract: Despite recent attention devoted to the development of individualized care in nursing homes, empirical research assessing changes in practice is quite limited, and very few studies have explored specifically the experiences and perceptions of certified nurse aides (CNAs). This study reports findings from a comparative analysis conducted on a data set including quantitative and qualitative data from CNAs (N = 289) and nurses in Connecticut (N = 245). Measures of obstacles to individualized care and needs for fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Two studies found that, in the absence of adequate staffing, caregivers often cut corners in care delivery (Bowers & Becker, 1992;Riggs & Rantz, 2001). The constrained fiscal resources in nursing homes and the regulated environment may also prevent optimal practice patterns (Aday & Andersen, 1974;Schnelle, Cruise, Rahman, & Ouslander, 1998) while encouraging a rigid, static environment with high staff turnover, poor communication patterns, and difficult nurse recruitment (Caudill, & Patrick, 1989;Chopoorian, 1986;Cohen-Mansfield, 1997;Walker, Porter, Grunman, & Michalski, 1998).…”
mentioning
confidence: 97%
“…Two studies found that, in the absence of adequate staffing, caregivers often cut corners in care delivery (Bowers & Becker, 1992;Riggs & Rantz, 2001). The constrained fiscal resources in nursing homes and the regulated environment may also prevent optimal practice patterns (Aday & Andersen, 1974;Schnelle, Cruise, Rahman, & Ouslander, 1998) while encouraging a rigid, static environment with high staff turnover, poor communication patterns, and difficult nurse recruitment (Caudill, & Patrick, 1989;Chopoorian, 1986;Cohen-Mansfield, 1997;Walker, Porter, Grunman, & Michalski, 1998).…”
mentioning
confidence: 97%